Motivasi dan Hasil Belajar Siswa Pada Mata Pelajaran PAI Dengan Penerapan Model Pembelajaran PBL di SMA Muhammadiyah Padang Panjang - Fitra Lismawarti; Iswantir M; Zulfani Sesmiarni; Melyann Melani; Hidra Ariza (UMSU, 2022)
The initial problem that became the background of this research was the low motivation of students to learn and also there were still students who did not complete the PAI subject at SMA Muhammadiyah Padang Panjang. This research uses quantitative research methods with the type of experimental research. There are 30 students in the Experiment class and 29 students in the control class. This study was conducted to determine how the effect of the application of the Problem Based Learning (PBL) learning model on students' motivation and learning outcomes. Based on the research that has been carried out, the following results are obtained: (1) The application of the PBL model affects the motivation of class XI students at SMA Muhammadiyah Padang Panjang; (2) The application of the PBL model affects the learning outcomes of class XI students of SMA Muhammadiyah Padang Panjang. From the results of the research above, it can be concluded that the application of the PBL model has an effect on student motivation and learning outcomes in PAI subjects at SMA Muhammadiyah Padang Panjang.